Beyond Woodrow Wilson: the identity of the study of public administration in historical perspective - Rutgers, Mark R. (1997)
The study of public administration is not as new as often supposed. In the 17th century, cameralism or polity sciences emerged, dealing with the proper administration to bring moral and economic well-being to people. The polity sciences flourished well into the 19th century. Questions concerning its topics and approach (legal, socioeconomical, or political), however, never were resolved. This historic forerunner of the study of public administration indicates that the lack of a clear identity is a characteristic feature of an interdisciplinary field. - Reproduced
Keywords: Public administration